New challenges for thailand: Labour and growth after the crisis - Mounier A. (2014)
Exploring the relationship between labour and economic growth in Thailand over the past half century, the article shows that Thailand can no longer rely on an extensive growth regime based on abundant and cheap labour. We argue that Thailand is at a critical juncture and that Thailand cannot avoid shifting to an intensive growth regime based on increases of labour productivity in order to control labour costs and, unlike past regimes, seek ways to ensure that the benefits of growth are better shared. ? 2010 Journal of Contemporary Asia.